2017
DOI: 10.1097/01.ogx.0000527580.35493.54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unilateral Tubal Abnormalities on the Results of Intrauterine Inseminations

Abstract: (Abstracted from Reprod Biomed Online 2017;35:314–317) While intrauterine insemination (IUI) is one of the first lines of infertility treatments and assisted reproductive techniques, the mean delivery per insemination rate is 10.7% and varies widely from one center to another, according to the French registry. This variation could be attributed to the heterogeneity of the treated population, especially with regard to fallopian tube status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Overall, these results support the theory that obstruction of only one tube plays a limited role in subfertility. These findings contrast those of a large retrospective study that reported significantly higher PR/cycle and CPR among patients with bilateral tubal patency, compared with unilateral tubal occlusion (16 versus 9% and 38 versus 20%, respectively) . No significant difference in cumulative live birth rates was found once adjusted for age, body mass index (BMI), infertility duration, and number of IUI cycles, however.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, these results support the theory that obstruction of only one tube plays a limited role in subfertility. These findings contrast those of a large retrospective study that reported significantly higher PR/cycle and CPR among patients with bilateral tubal patency, compared with unilateral tubal occlusion (16 versus 9% and 38 versus 20%, respectively) . No significant difference in cumulative live birth rates was found once adjusted for age, body mass index (BMI), infertility duration, and number of IUI cycles, however.…”
Section: Discussionsupporting
confidence: 91%
“…Following the removal of duplicates, 148 remained and each title and abstract was reviewed by two reviewers. Subsequently, 73 full texts were selected for full review and an additional 63 were excluded, leaving ten studies for quantitative analysis . Reasons for exclusion included case reports, non‐English articles, systematic reviews, and studies that failed to screen and exclude cases of male/female infertility, studies that did not specify the diagnostic method of diagnosing women with tubal block, and studies that did not report pregnancy outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the technique of IUI-D has been improving, the success rate of IUI-D is still low and unsatisfactory [6]. Many factors have been veri ed to in uence the outcome of IUI-D, including the women's age [7,8], an extreme body mass index, decreased ovarian reserve, primary infertility, unilateral tubal occlusion, pelvic adhesions and mild endometriosis [9][10][11][12][13], insemination times in a cycle [14] and semen factors (volume, motility and morphology of donor's semen) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the technique of IUI-D has been improving, the success rate of IUI-D is still low and unsatisfactory [6]. Many factors have been veri ed to in uence the outcome of IUI-D, including the women's age [7,8], an extreme body mass index, decreased ovarian reserve, primary infertility, unilateral tubal occlusion, pelvic adhesions and mild endometriosis [9][10][11][12][13], insemination times in a cycle [14] and semen factors (volume, motility and morphology of donor's semen) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%